Analysis of sea ice conditions and navigability in the Arctic Northeast Passage during the summer from 2002-2021 - Xiaoping Pang; Chenlei Zhang; Qing Ji; Yizhuo Chen; Zeng Zhen; Yamin Zhu; Zhongnan Yan (Geo-spatial Information Science, 2023)
ABSTRACTThe decreasing of Arctic sea ice is projected to continue with global warming, which makes the summer navigation conditions of the Arctic improve. Based on the multi-source remote-sensing data with inter-sensor calibration processing and the ship-based observational data from R/V Xuelong and M/V Yongsheng, the sea ice conditions of the Arctic Northeast Passage (NEP) during the 2002–2021 summer seasons were analyzed, and the navigability of the NEP between July and October from 2002 to 2021 was discussed. Inter-sensor calibration could effectively reduce the deviation from different passive microwave data. Sea ice extent and thickness in the NEP decreased annually, which resulted in the navigability of the NEP showing a potential tendency toward improvement in navigability. The navigation period was mainly concentrated in early August to early October. The middle part of the NEP was primarily affected by sea ice. This influence decreased over time, while the navigation period increased, especially in the Vilkitsky Strait, which is a key shipping area. This analysis of sea ice conditions and navigability in the past 20 years could provide a reference for future scientific investigations and aid in merchant ship navigation in the Arctic summer.